Prototype Internet of Thing Menggunakan Esp8266 pada Rangkaian Sistem Monitoring Penyiraman Lahan Petani - Didik Aribowo; Yogi Ramadani; Meisya Dwi Rizkiana; Nurma Lestari; Marsela Triana; Tita Nurdiyah; Sandi Sandi; Agus Prasetyo; Wildan Muzaki; M. Elan Maulana (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
This study aims to design and develop a prototype of an Internet of Things (IoT)-based land watering monitoring system using the ESP8266 module and soil moisture sensor. This system is designed to help farmers manage watering automatically based on soil moisture conditions, so that they can save water and labor. The process at this time begins with a literature study, hardware and software design, to prototype testing on two soil conditions, namely dry and wet. Data from the sensor is sent in real-time to the IoT platform, if the soil is detected dry, the system automatically activates the water pump. The results of the test show that the sensor works accurately in distinguishing soil conditions, and the system is able to water automatically according to needs. Furthermore, this system can also be monitored and controlled remotely via the internet. The conclusion of this study shows that the use of IoT technology is very potential to increase efficiency and effectiveness in agricultural land management.